Sharia Banking Internal Auditors' Perceptions Regarding the Influence of Auditors' Sharia Knowledge Education on the Effectiveness of Sharia Compliance Inspections - Was'an, Guruh Herman (PT Inovasi Pratama Internasional, 2024)
Islamic banks need to ensure that their operations comply with sharia principles to increase loyalty and satisfaction of sharia bank customers. Internal audit has one of the functions of ensuring sharia compliance has been fulfilled in sharia banking by carrying out sharia compliance checks. One of the challenges in internal audit in carrying out its function is the lack of qualified sharia auditors who have adequate sharia knowledge. In this context, education in sharia science for auditors becomes very relevant. This research aims to identify the influence of formal and non-formal sharia education for auditors on increasing the effectiveness of auditing compliance with sharia principles in sharia banking according to the perception of internal auditors. The method used is a quantitative method by distributing questionnaires to internal auditors in conventional commercial banks that have Sharia Business Units. Based on the results of this research, the variable perception of formal sharia science education does not have a significant effect on the effectiveness of sharia compliance checks, the perception of non-formal sharia science education has a significant effect on the effectiveness of sharia compliance checks. Furthermore, simultaneously the variables of perception of formal sharia education and non-formal sharia science education have a significant effect on the effectiveness of sharia compliance.